Multiple Organ Dysfunction Syndrome- Clinical Profile, Associations and Outcome in Critically ill Children Aged 1 Month to 14 Years Admitted to PICU in Nobel Medical College Teaching Hospital in Biratnagar - Giri, Arun; Yadav, Sunil Kumar; Sah, Vijay; Niroula, Niraj; Singh, Binayak (Birat Journal of Health Sciences, 2019)
Introduction: Multiple organ dysfunction syndrome (MODS), characterized by a progressive physiologic dysfunction involving two or more organ systems after an acute threat to systemic homeostasis, is not a rare entity among patients admitted to the pediatric intensive care units. Despite recent advances made in the medical technology and newer treatment strategies, large numbers of deaths in the PICU are attributable to MODS. Objective: To describe the clinical profile of MODS among children admitted in PICU and to observe its associations and outcome. Methodology: A hospital based prospective observational study was conducted in PICU of Nobel medical college teaching hospital, Biratnagar, Nepal from June 2017- May 2018. Children aged 1 month to 14 years admitted in the PICU with various medical and surgical illnesses were included in the study. All variables defining MODS and the data showing the presence or absence of sepsis were collected within 1 hour of admission (day 0) and then every day until transfer or discharge from PICU or until patient’s death. Results: Out of 150 admissions in the PICU, 103 fulfilled the inclusion criteria, and were enrolled in the study. A total of 53 patients (51%) developed MODS at some time during their stay at PICU and 88.7% of them had it at the time of admission. Of 103 cases under study, 26 died (mortality rate = 25.2%) and 92.3% of deaths were attributable to MODS. Children with neurological involvement had the highest risk of death [odds ratio (OR), 19.8; 95% confidence interval (95%CI), 4.37-90.30]. 75.5% of children with MODS had some sort of infection and 49% of them had sepsis. Conditions like SIRS, Sepsis, Severe sepsis, Septic shock and ARDS in the study patients were found significantly associated with MODS. Conclusion: A MODS is a common clinical entity among patients admitted to the PICU and are associated with significant mortality and morbidity. In children, MODS usually seem to develop early and in a simultaneous way. In developing countries like ours, morbidity and mortality associated with MODS in the PICUs is higher than that in the developed countries. Prevalence of sepsis in children with or without MODS is greater in the developing countries. Sepsis is further responsible for larger number of deaths in PICU.